What Works for Patients in Outpatient Treatment for Alcohol Addiction? An Explorative Study into Clients' Evaluation of Subjective Factors and Therapy Satisfaction - Katrin M. Frick; Barbara Loessl; Rigo K. Brueck; Levente Kriston; Andreas Jaehne; Dieter Riemann; Horst Gann; Anil Batra; Norbert Wodarz; Karl F. Mann; Michael M. Berner (SAGE Publishing, 2011)
This explorative survey investigated clients' evaluation of therapy elements and other supportive factors within a randomized controlled trial. The treatment of patients with alcohol dependence consisted of pharmacotherapy (acamprosate/naltrexone/placebo) and biweekly medical management (MM). Forty-nine study participants were surveyed with a questionnaire to measure both the patients' satisfaction with the therapy and the subjective assessment of treatment elements and supportive factors. Study participants were highly satisfied with the treatment. The supportive factors previously identified by Orford et al 1 were confirmed. 'Pharmacotherapy' was rated significantly less effective than 'MM' and 'global study attendance' ( P < 0.001). The significant differences in the evaluation of treatment elements point to a preference for regular low-key contacts rather than for medication. Such contacts based on MM could be a useful intervention in clinical care, and its effectivity should be examined more closely in further research.